True Blood - Understanding the impact of reduced oxygen carrying capacity using a physiological, haematological and metabolomics perspective - Lawler, N. (Murdoch University, 2018)
Oxygen carrying capacity has a positive association with endurance performance. As such, techniques such as altitude training can increase red cell mass (Hbmass) and have been shown to improve sea level performance. In addition to haematological changes (i.e. Hbmass), hypoxia can have a metabolic influence (e.g. increased oxidative and anaerobic enzyme concentration) resulting in changes to metabolites, which reflect systems level adaption to low oxygen carrying capacity environments. The use of metabolomics; therefore, represents an ideal analytical method to examine the physiological adaptations to hypoxia as this technique provides the ability to simultaneously analyse large number of metabolites present in human biological samples. The purpose of this thesis was to examine the acute (14 d) and chronic (42 d) influence of low oxygen carrying capacity on performance (Chapter Four), haematology (Chapters Three, Four and Five) and the metabolic profile (Chapter Three and Five).